Climate and Disaster Resilience of Greater Dhaka Area : A Micro Level Analysis - World Bank (Dhaka, Bangladesh, 2015)
Megacity Dhaka encounters various kinds of natural disasters quite frequently owing to its geographical location and a number of other physical and environmental conditions including low topography, land characteristics, multiplicity of rivers and the monsoon climate. Climate and disaster resilience is not the same in all parts of a city. Spatial variations in resilience patterns result from differences in the strengths and weaknesses of the city’s economic, social, physical, institutional or natural aspects across its various parts. Traditional frameworks to assess adaptive capacity at the local level have focused largely on assets and capitals as indicators. While useful in understanding the capacity of a system to cope with disasters and adapt to changing environments, asset-oriented approaches overlook the processes and functions of a system (for example, governance system, community participation in decision-making, knowledge dissemination and management, structure of institutions and entitlements etc.) that are important aspects influencing the capacity of a human system to respond to climate change events.